Antimicrobial activities of Cu(II), In(III), and Sb(III) complexes of N-methyl-N–phenyl dithiocarbamate complexes - Timothy O. Ajiboye (Elsevier, 2021)
Dithiocarbamate compounds have interesting biological features, and have been considered as an alternative to conventional antibiotics in order to mitigate the spread of antimicrobial resistance. This accounts for the growing interest in the investigation of the antimicrobial potency of different dithiocarbamate compounds. In this study, the antimicrobial activities of Cu(II), In(III), and Sb(III) complexes of N-methyl-N–phenyl dithiocarbamate complexes were evaluated against ten bacteria species, comprising of both Gram positive [(Bacillus cereus (ATCC 10876), Enterococcus faecalis (ATCC 29212), Enterococcus gallinurium (ATCC 700425), Listeria monocytogenes (ATCC 19115), Listeria monocytogenes, Staphylococcus aureus (ATCC 25923)] and Gram negative [(Escherichia coli O177, Klebsiella pneumoniae, Salmonella enterica and Salmonella Typhimurium)]. Three techniques; disc, well diffusion, and microdilution were explored to assess antimicrobial activity of dithiocarbamate compounds. The results showed good antimicrobial activities for both the ligand (ammonium N-methyl-N-phenyl dithiocarbamate)) and complexes against Gram positive and Gram negative bacteria, with average zone of inhibition for disc and well diffusion ranging from 7.00 ± 1.000 to 17.67 ± 1.528 mm and 7.67 ± 0.577 to 19.33 ± 1.528 mm, respectively. The ligand and antimony complex displayed pronounced zone of inhibition against all the bacteria species, with multidrug resistant E. coli being the most sensitive species. The minimum inhibitory concentration (MIC) of the four dithiocarbamate compounds (the ligand and the three complexes) against all the bacteria species ranged from 0.022 ± 0.045 to 2.522 ± 0.045 µg/mL. The lowest MIC values were observed for antimony and copper complexes against L. monocytogenes, while the indium complex and the ligand showed lowest MIC values against S. enterica and S. aureus, respectively. This suggests that these dithiocarbamate compounds could be the best candidates to be used for the development of new antimicrobial compounds for the treatment of multidrug resistant bacteria infections.